University librarians from Bălţi build institutional capacity (Confluenţe Bibliologice, 2025)
Scientiﬁc Library of Alecu Russo Bălţi State University will create new conditions and info-library services for university community members through their participation in International project ERASMUS + capacity building in higher education - capacity Building in the ﬁeld of higher education (CBNE) - Library network - support Services: modernization of libraries in Armenia, Moldova and Belarus (2015 -2018) together with academic libraries in Armenia, Belarus and the Library of the Academy of Public Administration in Moldova.
Keywords: international projects; LNSS project; dissemination of information; modernization of libraries